KEBERAGAMAN YANG MENYAPA STUDI ANALISIS TERHADAP FIQH IKHTILAF HASAN AL-BANNA - Daipon, Dahyul (Alhurriyah, 2010)
The difference is sunnatullah or the Godâ€™s certainty and fitrah (tithe). Allah SWT has explained in the holy Qurâ€™an that human being is created from such kinds of ethnics, nations, skin colors also different language. On the other hand, the difference is a Godâ€™s mercy for all human beings even for Moslems, thus they have freedom of certain attitudes. On the other way, the unification competes with the natural law itself. Since the prophet era until now, the difference will be emerging even ever after. The caliph Umar bin Abdul Aziz said that â€œI even hate if some companions of Prophet Muhammad were not being at odds with each others. If they had no any differences each others, then we ould never have any dispensations (rukhsah).â€ Imam Syahid Hasan Al-Banna as a leader of a missionary endeavor (dakwah) stated on his written that he believed if the difference (ikhtilaf) in the case of branch (furu)â€™ was a must that would happen. So that, the efforts for managing and organizing to shape the difference (ikhtilaf) being a positive energy was an urgent effort that must be done at the time. His success for leading an organization of missionary endeavor (dakwah) of Ikhwanul Muslimin was very affected by his wisdom for managing and organizing the difference (ikhtilaf) in his era.